Effect of Age on Diabetogenicity of Alloxan in Ossabaw Miniature Swine - Badin, Jill K (Comp Med, 2019)
According to a single study in dogs that was conducted in 1949, the diabetic effects of the β-cell toxin alloxan are dependent on age. The current study examined whether this age-dependence of alloxan is present in the clinically relevant Ossabaw miniature swine (Sus scrofa domestica) model of metabolic syndrome. Juvenile swine (n = 8; age, 4.3 ± 0.2 mo) and adult swine (n = 8; age, 7.4 ± 0.2 mo) received alloxan (average dosage, 140 mg/kg IV) and were placed on a hypercaloric, atherogenic diet for 6 mo. The metabolic syndrome profile was confirmed by measuring body weight, cholesterol, and triglycerides. Intravenous glucose tolerance testing was used to assess glucose clearance and peripheral plasma insulin levels. The β-cell mass was calculated by immunohistochemical staining of pancreatic tissue. Although juvenile and adult swine exhibited comparable severity of metabolic syndrome, adult swine developed impaired glucose clearance and elevated fasting blood glucose levels at 6 mo after alloxan administration on the atherogenic diet. Peripheral plasma insulin levels in juvenile and adult swine were comparable at all time points and lower than in nonalloxan-treated age-matched controls, which is reflected in the lower pancreatic β-cell mass of the 2 treated groups. However, compared with adult pigs, juvenile swine exhibited greater insulin response recovery (complete or partial restoration of peripheral insulin levels to reference values) at 6 mo after alloxan administration. Overall, these results indicate that youth can confer some protection against the diabetogenic effects of alloxan in swine, potentially due in part to the greater insulin response recovery of young pigs. This study supports previous research that the effects of alloxan are dependent on the developmental maturity of the animal.